The impact of inflation and foreign exchange fluctuation on manufacturing sector: comparison between Malaysia and Singapore / Nadia Kamarul Ariffin - Kamarul Ariffin, Nadia (2007)
Several studies show that certain companies were uniquely affected by the changes of Consumer Index (CPI) and foreign exchange (FOREX) fluctuation. This project paper tries to find the effect Of inflation and FOREX fluctuations on manufacturing sector by comparing the impact in Malaysia and Singapore. This Study tries to achieve two Objectives; (l) to identity the correlation of inflation fluctuations on the manufacturing sector. and (2) to identify the correlation or exchange rate fluctuations on the manufacturing Sector. The independent variables were the quarter CPI rates and the quarter exchange rates from 1996 to 2005. while the dependent variables were 40 companies' return on equity from Malaysia and Singapore